KEADILAN PAJAK UMKM DALAM PERSPEKTIF TEORI RAWLSIAN: ANALISIS PADA INDIVIDUAL DAN CORPORATE TAX DI INDONESIA - Al Huda, Nabilah Hakimah; Furqon, Imahda Khoiri (Journal of Financial and Tax, 2026)
This article aims to analyze tax fairness for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia through the perspective of John Rawls’ theory of justice. This study a qualitative method with a literature review approach that examines academic literature, tax regulations, and previous research results to assess the suitability of tax policies with the principle of justice as fairness. The analysis focuses on two of Rawls’ main principles, namely equal liberty and the difference principle, to evaluate the extent to which the Indonesian tax system, particularly through Government Regulation No. 23 of 2018, Government Regulation No. 55 of 2022, and the Tax Regulation Harmonization Law, reflects the value of distributive justice. The results of the study show that although the MSME tax policy has provided concessions and incentives for small businesses, inequalities in digital access, tax literacy, and administrative capacity remain major obstacles to the realization of substantive fiscal justice. The important findings of this study confirm that the application of Rawls’ theory of justice can serve as a normative basis for improving tax policy to be more inclusive, proportional, and favorable to economically disadvantaged groups, while strengthening the moral function of taxation as a tool for social welfare redistribution.